A Debt Servicing and Its Implications for Public Investment: Special Reference to Nigeria Economy - Ademola Ishola; S. A. Ishola; S. O. Bamisaye (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2026)
This paper reviews the relationship between debt servicing and public investment in Nigeria, analyzing how the nation's debt obligations influence its capacity to fund public projects. Utilizing data from various studies, the analysis reveals that increasing debt service payments can significantly inhibit public investment, thereby affecting economic growth and development.